SOME NOTES ABOUT THE NATURE RESERVE PULAU PANAITAN (PRINSENEILAND) IN STRAIT SUNDA, with special reference to the avifauna - A HOOGERWERF (BRIN Publishing (Penerbit BRIN), 1953)
Fro!ll August the 30th till October the 5th 1951, Kebun Raya Indonesia (Botanical Gardens) at Bogor organized an expedition to the islandmentioned above. Up till then the island was nearly